The Relationship between the Bandwagon Effect and Students' Career Decision Making at Taruna Satria Vocational School, Pekanbaru - Fitri Muslimah; Mhd. Subhan (AMK : Abdi Masyarakat UIKA, 2026)
This study aims to analyze the relationship between the bandwagon effect and career decision-making among students of SMK Taruna Satria Pekanbaru. This phenomenon is motivated by the tendency of students in determining career choices that are not entirely based on personal considerations, but are influenced by social environments such as peers, family, and trends in social media. This study uses a quantitative approach with a correlational research type. The study population was 150 students with a sample of 60 students determined through the Slovin formula with a simple random sampling technique. The research instrument used a Likert scale questionnaire that has been tested for validity and reliability. The data analysis technique used Spearman Rank correlation because the data was not normally distributed. The results showed that the level of bandwagon effect was in the fairly high category of 41.7%, while career decision-making was in the fairly high category of 50%. The results of the correlation test showed a coefficient value of 0.508, which means there is a positive relationship with a moderate level of strength between the bandwagon effect and career decision-making. This finding indicates that the higher the tendency of the bandwagon effect, the greater the influence of the social environment in the student's career decision-making process.